The Application of Arduino-Based Line Follower Robotics Technology as a Tool to Enhance Students' Self-Efficacy - Slamet Kurniawan Fahrurozi; Muhammad Hassan Massaty; Cucuk Wawan Budiyanto; Bayu Sutanto (Universitas Sebelas Maret, 2025)
This study focuses on a detailed analysis of the Robotics Self-Efficacy Test, aiming to evaluate its effectiveness in measuring students' confidence levels across specific robotics tasks. Using robotics as a learning medium, this research enhances student engagement and practical skills in technical areas. Addressing a gap in precise self-efficacy measurement tools for robotics education, the study employs the RSE-Test to assess confidence in essential robotics tasks, such as robot assembly, programming, and control. Data collection involved a 10-item RSE-Test questionnaire completed by 30 students engaged in robotics activities, followed by a statistical analysis to calculate mean scores, standard deviations, item-total correlations, and Pearson correlational analysis. The overall mean score was 3.9835, indicating high confidence, with a pooled standard deviation of 0.687, showing minimal variation. The pooled Standard Error of the Mean was 0.128, reflecting high precision in estimating the overall mean. Cronbach’s Alpha of 0.810 confirms the test's strong internal consistency, and item-total correlations ranged from 0.423 to 0.703, supporting the reliability of the RSE-Test. Pearson correlation analysis revealed significant relationships between items, further validating the tool. Results indicate high self-efficacy in basic robotics tasks, although students showed slightly lower confidence in more advanced tasks, suggesting areas for further support. This study validates the RSE-Test as an effective tool for measuring self-efficacy in technical education, emphasizing the role of foundational skills in building student confidence. The findings provide valuable insights for curriculum developers, suggesting the need for targeted support in advanced robotics tasks.